2023
DOI: 10.2147/jir.s404591
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Peripheral Blood Cell Ratios in Primary Membranous Nephropathy: A Single Center Retrospective Study

Abstract: Background: Primary membranous nephropathy (PMN) is a common cause of nephrotic syndrome in adults. Forty percent of the patients continue to progress and eventually develop into chronic renal failure. Although phospholipase A2 receptor (PLA2R) is the major antigen of PMN, the clinical features do not often parallel with the antibody titers. Therefore, it is significant to find relative credible markers to predict the treatment response. Methods: One hundred and eighteen PMN patients were recruited. The respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…We also found that patients with a long course of disease had a poor response to treatment, which may be due to the persistence of chronic inflammation, resulting in increased deposition of immune complexes on the outside of the glomerular basement membrane, massive formation of basement membrane “spike” and thickening of the basement membrane, thereby aggravating renal injury and leading to poor prognosis [ 35 , 36 ]. Moreover, studies had shown that immune-inflammation index and monocyte-lymphocyte ratio were reliable markers which might be used to predict prognosis for IMN patients [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that patients with a long course of disease had a poor response to treatment, which may be due to the persistence of chronic inflammation, resulting in increased deposition of immune complexes on the outside of the glomerular basement membrane, massive formation of basement membrane “spike” and thickening of the basement membrane, thereby aggravating renal injury and leading to poor prognosis [ 35 , 36 ]. Moreover, studies had shown that immune-inflammation index and monocyte-lymphocyte ratio were reliable markers which might be used to predict prognosis for IMN patients [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%